2010 IEEE MTT-S International Microwave Symposium 2010
DOI: 10.1109/mwsym.2010.5517375
|View full text |Cite
|
Sign up to set email alerts
|

A novel passive wireless ultrasensitive RF temperature transducer for remote sensing

Abstract: A wireless passive ultrasensitive temperature transducer is presented in this paper. The transducer consists of micro bimorph cantilevers (Aluminum-Silicon) and split ring resonators, operating at millimeter wave frequencies around 30 GHz. As the temperature changes, the bilayer cantilevers deflect and thus alter the resonant frequencies of the resonators. The design achieves a sensitivity of 1.05 GHz/um with respect to cantilever deflection, corresponding to a sensitivity of 150 MHz/oC, three orders of magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This is because some of the used substrate materials and/or constructed sub-wavelength structures have high temperature sensitive property. According to the sensing mechanism of resonant-type metamaterial-inspired sensors mentioned above, the temperature sensitive dielectric substrate materials and the sub-wavelength nano/micro mechanical structure with thermal expansion coefficient differences will result in the changings of resonant frequency/strength under different temperatures [38][39][40][41][42].…”
Section: Metamaterial-based Temperature Sensing Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…This is because some of the used substrate materials and/or constructed sub-wavelength structures have high temperature sensitive property. According to the sensing mechanism of resonant-type metamaterial-inspired sensors mentioned above, the temperature sensitive dielectric substrate materials and the sub-wavelength nano/micro mechanical structure with thermal expansion coefficient differences will result in the changings of resonant frequency/strength under different temperatures [38][39][40][41][42].…”
Section: Metamaterial-based Temperature Sensing Technologymentioning
confidence: 99%
“…Based the different thermal expansion coefficients of different substrates used in the metamaterials, the bending deformations due to the changes of background temperature will alter the equivalent capacitance/inductance parameters of the meta-atom, thereby causing the resonant frequency shift or resonance strength change. For examples, Thai et al firstly loaded a cantilever arm at the open slot of the metal SRR as shown in Figure 1A-i [38,50]. The arm consisted of two layers of heterogeneous materials with different thermal expansion coefficients.…”
Section: Temperature Sensing Based On the Thermal Expansion Coefficient Differencementioning
confidence: 99%
See 1 more Smart Citation
“…These applications require that the sensor is easy to fabricate, cheap, small, easy to integrate and highly reliable. However, most existing solutions require a power source or have low temperature limitations [1][2][3]. Optical based wireless sensors were developed but the accuracy was not satisfactory [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [10] have developed a resonator/antenna based wireless temperature sensor and reported test results at 1000°C. Thai et al [1] used micro-bimorph cantilevers to develop an ultrasensitive temperature sensor working at a high frequency of 30 GHz. Metamaterials have drawn significant attention lately because of their ability to display extraordinary properties such as negative refractive index, reverse Doppler effect etc.…”
Section: Introductionmentioning
confidence: 99%